Parental stress: a study from a pediatric intensive care unit in Mangalore - Kumar, Binoop Sampath; Avabratha, K. Shreedhara (International Journal of Contemporary Pediatrics, 2017)
Background: Pediatric intensive care unit (PICU) is a highly stressful environment to most parents. Knowledge of stress allows us to plan counselling strategies for the suffering parents. The objectives were to identify common parental stressors during their child’s critical illness and to examine the relationship of demographic variables with their stress. Methods: It was a prospective observational study done in PICU of a tertiary care medical college hospital in Mangalore. One hundred parents of children (1 month to 15 years) admitted to PICU for at least 24 hours were interviewed using the Parental Stress Scale (PSS: PICU), which rates 22 factors on a scale from 1 (not stressful) to 5 (extremely stressful). The demographic and clinical characteristics of children were also recorded and analysed statistically. Results: The average parental stress score was 3.5. The main causes of extremely stressful situations were the sight of their child being unresponsive, sight of monitors & equipment in PICU, other sick children in PICU, crises in other children in the PICU. Parents of children who got admitted in PICU for the first time were more stressed. Younger parents were more stressed than older parents, irrespective of the illness and clinical status. Age of the child, sex, socioeconomic status, urban/rural, father/mother did not vary stress levels, all had similar stress level (score>3). Among the procedures, majority (52%) parents felt intravenous cannulation as more stressful followed by blood sampling (43%). Conclusions: Young parents and first PICU admission were more stressful. Socioeconomic status, residential area and age of children did not affect level of stress. Many of these stress factors can be looked into and remedial steps can be taken to relieve some of these stressors.